Serial warfare in al-maghrib and al-andalus (8-11TH centuries CE) based on record of Spanish islam by reinhart dozy (1820-1883CE) - Jamsari E.A.; Talib N.M.; Abdullah S.; Adibah Sulaiman (IAEME Publication, 2024)
Indexed by Scopus